Perspective of a Provisionally Registered Pharmacist (PRP) during Inpatient Pharmacy (IPD) rotation / Nur Ainin Sofiya Mohamad Irwan and Janattul Ain Jamal - Mohamad Irwan, Nur Ainin Sofiya; Jamal, Janattul Ain (Faculty of Pharmacy, 2023)
An 8-week period has elapsed with multiple work episodes in between. On the first day I had no idea whether I would get any sense of enjoyment from my rotation at the inpatient pharmacy (IPD). Now, I experienced ambivalent emotions but was profoundly grateful for the invaluable experiences. Upon reflection, the early days began with a two-week orientation, or they called it ‘tagging-week’. As a provisionally registered pharmacist (PRP), I had to undergo counselling validation and basically gained a comprehensive understanding of the workflow and systems of the IPD, and the roles and responsibilities of an IPD pharmacist. Initially, the overwhelming feeling hit due to the requirement to adapt with the ‘fast’ working pace, with a steep learning curve. Nevertheless, with time, I successfully adapted to the working pace, and managed to execute multiple tasks simultaneously. The first four weeks back in April did not afford me the opportunity to fully appreciate this rotation, but now, I consider it as the most priceless moment in life. I was in a situation where various information was thrown into my mind at once, all of which was crucial for me to promptly comprehend and assimilate, and I’m thankful I managed to handle the situation and it has positively shaped me becoming who I am right now.